Tablet PC: a way of replacing english teaching materials in a small class - Riera Cambisaca, Byron Fabricio; Sangurima Cajamarca, Daysi Verónica
Nowadays, we have a recognizable difficulty which shows a significant reduction in the quality of teaching English as a second or foreign language. This difficulty is the avoidance of using English teaching materials to present a lesson. In some cases, the teacher would avoid using these resources because of the lack of support by the different educational institutions and the difficulties of bringing them to several classes. Therefore, this project shows that there are more advantages than disadvantages of replacing traditional English teaching materials with a technological device called the Tablet PC. Using audiovisual and authentic teaching materials is important to enhance the students? learning process. They motivate students to use the target language in a real context. Also, including technology in the classroom is a good way to stimulate students because they are familiar with it; therefore, the application of the Tablet PC is a revolutionary way to make the lesson more interesting and efficient. English teachers could replace several traditional resources such as, audio players, video players, pictures, presentations, and others for this technological device which of course demands some previous knowledge about its technical aspects. Facilitators will notice that there are more strengths than weaknesses of utilizing the Tablet PC in the classroom thanks to the results of the lesson plans applied to twenty-three students of San Isidro Institute. In addition, it is important for English educators to notice the recommendations before using this device in order to enrich their teaching.